About graphic design - Hollis, Richard (London : Occasional Papers, 2012)
Featuring a comprehensive selection of writings by renowned graphic designer, graphic design theorist and historian Richard Hollis, this densely illustrated book includes a wide array of interviews, essays, letters, articles and lectures. It covers virtually everything regarding the field and history of graphic design, from Soviet revolutionary posters and designers in Nazi Germany to Penguin book covers, New 'New' Typography, Max Bill and Nicolete Gray. Various texts on Robin Fior, Theo Ballmer, Uwe Loesch and Pierre Faucheux, among many others, add depth to this very thoroughly researched story of graphic design.
boek